2019
DOI: 10.3390/j2030024
|View full text |Cite
|
Sign up to set email alerts
|

Does Qigong Practice Have Benefits on the Management of Parkinson’s Disease?

Abstract: Parkinson’s disease (PD) is a progressive neurological disorder leading to loss of autonomy and a decline in quality of life. Qigong, a practice rooted in traditional Chinese medicine, has been positively reported on a variety of complaints of chronically ill patients and on gait imbalance in the elderly. PubMed and B-On databases were accessed during March 2018 to carry out an inventory of relevant scientific papers relating PD to Qigong. Fifteen articles were found and analyzed allowing us to highlight that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The authors have also demonstrated that both self-selected and fast gait speed were strong predictors of falls (six-month history of falls) with a cut-off of 0.98 m/s and 1.32 m/s, respectively, which indicates that our participants would be very unlikely to be at risk of falling after the intervention. Improvements observed in gait speed were comparable to Tai Chi [ 31 , 62 ] and BDJ [ 28 , 29 ] interventions. A recent systematic review in PD [ 39 ] has failed to detect an effect on gait speed following virtual reality rehabilitation trainings, in comparison to conventional or traditional rehabilitation trainings, although a significant effect has been observed on stride length, balance, and mobility.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The authors have also demonstrated that both self-selected and fast gait speed were strong predictors of falls (six-month history of falls) with a cut-off of 0.98 m/s and 1.32 m/s, respectively, which indicates that our participants would be very unlikely to be at risk of falling after the intervention. Improvements observed in gait speed were comparable to Tai Chi [ 31 , 62 ] and BDJ [ 28 , 29 ] interventions. A recent systematic review in PD [ 39 ] has failed to detect an effect on gait speed following virtual reality rehabilitation trainings, in comparison to conventional or traditional rehabilitation trainings, although a significant effect has been observed on stride length, balance, and mobility.…”
Section: Discussionmentioning
confidence: 61%
“…The BDJ form of Qigong exercise has an advantage over other modalities of training programs due to its positive balance between desirable characteristics for home-based physical interventions (cost-effective, simple, self-paced, safe, of low intensity and duration, and not requiring additional equipment or a large space) and potential beneficial effects [ 26 , 27 , 28 , 29 , 59 ]. Due to these characteristics, Qigong-based exercises have been investigated in patients with PD and have been proven promising to alleviate non-motor and motor-related symptoms and their associated functional outcomes [ 28 ]. Additionally, it appears to have a significant impact on reducing levels of anxiety and depression in people with physical or mental conditions [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects can be achieved through specific Qigong techniques, such as “White-Ball” in the Heidelberg model of TCM [ 93 , 103 ]. Qigong practice benefits have been shown on different components of wellbeing, such as cognitive behavior, distraction, social interaction, cardiovascular fitness, amine regulation and endorphin regulation [ 91 , 104 , 105 , 106 ]. This practice generally provides a non-pharmacological modality for achieving biopsychosocial health for those suffering from anxiety, stress, depression, symptoms, chronic pain, immunity, infection and reduced quality of life [ 91 , 106 , 107 , 108 , 109 , 110 ].…”
Section: Resultsmentioning
confidence: 99%